Endocytosis is required for consolidation of pattern-separated memories in the perirhinal cortex - Piromalli Girado, Dinka; Miranda, Magdalena; Giachero, Marcelo; Weisstaub, Noelia; Bekinschtein, Pedro (Frontiers in Systems Neuroscience, 2023)
The ability to separate similar experiences into differentiated representations is proposed to be based on a computational process called pattern separation, and it is one of the key characteristics of episodic memory. Although pattern separation has been mainly studied in the dentate gyrus of the hippocampus, this cognitive function if thought to take place also in other regions of the brain. The perirhinal cortex is important for the acquisition and storage of object memories, and in particular, for object memory differentiation. The present study investigates the importance of the cellular mechanism of endocytosis for object memory differentiation in the perirhinal cortex and its association with brain-derived neurotrophic factor, which was previously shown to be critical for the pattern separation mechanism in this structure. We used a peptide (Tat-P4) to block endocytosis and provide evidence from a molecular disconnection experiment that BDNF and endocytosis-related mechanisms interact for memory discrimination in both male and female rats.